2010
DOI: 10.1215/s12280-010-9146-x
|View full text |Cite
|
Sign up to set email alerts
|

Geneticizing Ethnicity: A Study on the “Taiwan Bio-Bank”

Abstract: Taiwan as an island country is an immigrant society where interethnic marriages have been common. In the past centuries, it has not been unusual that people in Taiwan change their ethnic identities for various reasons. Its "four great ethnic groups" (sida zuqun)-the Hoklo, Hakka, Mainlanders, and aboriginal peoples-exist only as a social construction that arose in the 1990s in a specific political-cultural context. In 2005, a major government-sponsored research project, the Taiwan Biological Sample Bank-or Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The Taiwan Biobank was launched in 2005 as part of Taiwan’s strategy to promote biomedicine and technology [ 29 ]. However, this project has been repeatedly criticized by specific human rights groups and legal scholars who have expressed concerns about genetic privacy, informed consent, linkage of databases, conflict of interest, procedural justice, and legitimacy of technology policymaking [ 53 ]. This has resulted in rigorous legislative and regulatory requirements as reflected in the HBMA and HRSA, which have limited the development of similar tissue storage or biobanking approaches and the access and utilization to such samples for the last few years.…”
Section: Elsi Practices In East Asiamentioning
confidence: 99%
“…The Taiwan Biobank was launched in 2005 as part of Taiwan’s strategy to promote biomedicine and technology [ 29 ]. However, this project has been repeatedly criticized by specific human rights groups and legal scholars who have expressed concerns about genetic privacy, informed consent, linkage of databases, conflict of interest, procedural justice, and legitimacy of technology policymaking [ 53 ]. This has resulted in rigorous legislative and regulatory requirements as reflected in the HBMA and HRSA, which have limited the development of similar tissue storage or biobanking approaches and the access and utilization to such samples for the last few years.…”
Section: Elsi Practices In East Asiamentioning
confidence: 99%
“…Scientific practices involved in research on race and ethnicity in health and genomics have been shown to be situated in and shaped by various specific national, sociopolitical, and historical contexts (Hinterberger, 2012;Epstein, 2010;Tsai, 2010;Olarte Sierra and Díaz Del Castillo Herná ndez, 2014). These national, sociopolitical, and historical contexts shape the ways in which ethnicity and race are enacted in research by prescribing, for example, the (official) categories which must be used in research -a process referred to as ''categorical alignment'' (Epstein, 2007) -or by defining which groups are and are not considered to be ethnic and racial minorities (Gissis, 2008;Helberg-Proctor et al, 2016, 2017Proctor et al, 2011).…”
Section: Researching Ethnicity In the Context Of Healthmentioning
confidence: 99%
“…Third, the discussions surrounding genetic uniqueness and homogeneity are closely related to questions of inclusion and identity, by which we mean that population characterizations rely heavily on developing selection criteria (Lipphardt, 2010; Prainsack, 2007: 85). For instance, in Taiwan the claim of the unique population requires balancing between the four main ethnic groups – groups that Tsai (2010) shows to be more hybrid and open to contestation than the practices of a population biobank in Taiwan would suggest. In Singapore, the uniqueness and claimed potential usefulness of the collection in Biopolis comes from the claim that it represents all of ‘Asia’ (Ong, 2016).…”
Section: Introductionmentioning
confidence: 99%